Feather degradation by keratinolytic bacteria and biofertilizing potential for sustainable agricultural production. (24th October 2018) - Tamreihao, K.; Mukherjee, Saikat; Khunjamayum, Rakhi; Devi, Laishram Jaya; Asem, Roshan Singh; Ningthoujam, Debananda S.
Abstract : Feathers account for 5–7% of the total weight of chicken have become one of the major pollutants due to their recalcitrant nature. Feather which is constituted of 90% keratin can be a good source of peptides, amino acids, and minerals for use as organic fertilizer. Traditional feather degradation methods consume large amount of energy and reduces the overall quality of the proteins. However, degradation of keratin by keratinolytic bacteria may represent as an alternative for the development of cheap, cost effective, eco‐friendly, and easily available nitrogen (N) and minerals rich source as potential organic fertilizers. Keratinase enzymes from bacteria are serine‐type proteases showing optimal activity at pH 6 to 9 and 30 to 50 °C. Mechanism of degradation includes, sulfitolysis, proteolysis, followed by deamination. Keratinolytic bacteria showing antagonism against important plant pathogens may act as biocontrol agent. Feather hydrolyzate can also be employed as nitrogenous fertilizers for plant growth. Tryptophan release from the feather degradation can act as precursor for plant phytohormone, indole‐3‐acetic acid (IAA). Solubilization of inorganic phosphate (P) by keratinolytic bacteria may further elevate the growth of plant. Application of hydrolyzate increases the water holding capacity, N, carbon (C) and mineral content of the soil. It elevates protein, amino acids, and chlorophyll content of plant. Feather hydrolyzate enhances seed germination and growth of plant. Soil application further increases the population of beneficial bacteria. The use of keratinolytic bacteria having antagonistic and plant growth promoting activities, and feather hydrolyzate can emerge as sustainable and alternative tools to promote and improve organic farming, agro‐ecosystem, environment, human health, and soil biological activities.